The Influence of Individual Characteristics, Occupational Health and Safety (K3) on Employee Work Productivity with Job Satisfaction as Intervening Variable: Pengaruh Karakteristik Individu, Kesehatan dan keselamatan kerja (K3) Terhadap Produktivitas Kerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening - Sodik, M Ali; Sumartik, Sumartik (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine individual characteristics, job characteristics, and occupational health and safety (K3) on productivity with job satisfaction Intervening Variable PT. Integra Indocabinet Sidoarjo. This research is a type of quantitative research with hypothesis testing. The sample used in this study were 75 employees of PT. Integra Indocabinet Sidoarjo. The analytical tool used in this research is partial least square (PLS). The results of this study prove that individual characteristics affect job satisfaction, job characteristics affect job satisfaction, job characteristics affect job satisfaction, individual characteristics affect productivity, job characteristics affect productivity, job characteristics affect productivity, job satisfaction affects productivity, Individual characteristics affect productivity mediated by job satisfaction, job characteristics affect productivity mediated by job satisfaction, job characteristics affect productivity mediated by job satisfaction.